GTP‐binding inhibitors increase LRRK2‐linked ubiquitination and Lewy body‐like inclusions. Issue 10 (17th March 2020) - Thomas, Joseph M.; Wang, Xiaobo; Guo, Gongbo; Li, Tianxia; Dai, Bingling; Nucifora, Leslie G.; Nucifora, Frederick C.; Liu, Zhaohui; Xue, Fengtian; Liu, Chunfeng; Ross, Christopher A.; Smith, Wanli W.
Abstract: Parkinson's disease (PD) is one of the most common movement disorders with loss of dopaminergic neurons and the presence of Lewy bodies in certain brain areas. However, it is not clear how Lewy body (inclusion with protein aggregation) formation occurs. Mutations in leucine‐rich repeat kinase 2 (LRRK2) can cause a genetic form of PD and contribute to sporadic PD with the typical Lewy body pathology. Here, we used our recently identified LRRK2 GTP‐binding inhibitors as pharmacological probes to study the LRRK2‐linked ubiquitination and protein aggregation. Pharmacological inhibition of GTP‐binding by GTP‐binding inhibitors (68 and Fx2149) increased LRRK2‐linked ubiquitination predominantly via K27 linkage. Compound 68‐ or Fx2149 increased G2019S‐LRRK2‐linked ubiquitinated aggregates, which occurred through the atypical linkage types K27 and K63. Coexpression of K27R and K63R, which prevented ubiquitination via K27 and K63 linkages, reversed the effects of 68 and Fx2149. Moreover, 68 and Fx2149 also promoted G2019S‐LRRK2‐linked aggresome (Lewy body‐like inclusion) formation via K27 and K63 linkages. These findings demonstrate that LRRK2 GTP‐binding activity is critical in LRRK2‐linked ubiquitination and aggregation formation. These studies provide novel insight into the LRRK2‐linked Lewy body‐like inclusion formation underlying PD pathogenesis. Abstract : It is not clear how Lewy body (cellular inclusion with protein aggregation) occurs in Parkinson's disease (PD). We demonstrated that pharmacological inhibition of GTP‐binding by GTP‐binding inhibitors (68 and Fx2149) increased leucine‐rich repeat kinase 2 (LRRK2)‐linked ubiquitination and protein aggregation predominantly via K27 linkage. These studies provide novel insight into the LRRK2‐linked Lewy body‐like inclusion formation underlying PD pathogenesis.